Confirmatory Factor Analysis to Measure Self-Efficacy and Outcome Expectation in Mathematics Learning - Cut Yuni Nurul Hajjina; Heri Retnawati (AlphaMath : Journal of Mathematics Education, 2022)
This study was conducted to analyze things that can have an influence on self-efficacy and outcome expectations in learning mathematics and to confirm the suitability of the model with the data using First order confirmatory factor analysis (1st Order CFA). The population in this study were students of SMA Plus Al Athiyah Aceh with a large sample of 53 students. The sample was selected based on a purposive sampling technique with the criteria that students with good, medium and low math achievement from each grade level. The research data were analyzed using the Linear Structural Model (LISREL) version 8.8 from Joreskog and Sorbom. The results of data analysis showed that the self-efficacy and outcome expectation instruments had good quality construct validity after eliminating the two items c3 and c5. Item c1 which is the belief in being able to correctly solve all math problems that the teacher gives most dominantly reflects self-efficacy in learning mathematics, while item d2 which feels it is important to learn mathematics most dominantly reflects the aspect of outcome expectation in learning mathematics.